Nuevo Corinto: A Chiefly Village in Northeastern Costa Rica - Salgado González, Silvia (2021)
Archaeological research at Nuevo Corinto has provided information on the emergence of complex village patterns in northeastern Costa Rica. This includes an improved chronology of in situ culture change over a 3000-year period. The consolidation of an architectural core began ca. AD 400-600 with the principal period of construction of circular elevated platforms for supporting domestic structures, reaching peak construction ca. AD 700-1100. Nuevo Corinto, together with neighboring sites, appears to have been a major node in trade networks extending from the Caribbean to the Pacific coasts. Our research has provided details on the emergence and growth of architectural units and hydraulic features in this village, a center of manufacturing, trade, and social hierarchy in the Caribbean lowlands.